1, 2, 3-- mar! - Fletcher, Julie; Gil, Carmen (Barcelona [Spain] : Combel Editorial, 2008)
Learn to count from one to five watching a dolphin, two turtles, three star fish, four sea horses, and five fish playing in the ocean.
Cover title.
On board pages.
Translation of 1, 2, 3, sea!
Keywords: Marine animals -- Juvenile fiction; Counting -- Juvenile fiction; Marine animals -- Fiction; Counting; Spanish language materials; Toy and movable books